Teaching and Learning Hyperbolic Functions (I); Definitions and Fundamental Properties - Teodor Dumitru Vălcan (PedActa, 2016)
We propose that in some papers (4 maybe 5 !) to present a model of teaching and learning in secondary education of hyperbolic functions, giving many properties (starting with fundamental ones and finishing with development in Tayler series), and then to present some of their applications in algebra and mathematical analysis. The papers addresses teachers in the teaching of these issues in the classroom, but also in preparing students to the school competitions .